Social Science Libraries. Interdisciplinary Collections, Services, Networks - Rudasill, Lynne M. (IFLA Publications, 2010)
This volume focuses on practical and empirical accounts of organizational change in the social sciences and impacts upon the professional skills, collections, and services within social science libraries. Section one focuses upon the question of interdisciplinary within social science libraries and the role of libraries to both react to and facilitate paradigm shifts in research and science. Section two focuses on the rise of data as a resource to be collected and shared within social science libraries. The third section focuses on the role of librarians to facilitate the development of social organizations that develop around new technologies and research communities.